THE EFFECT OF ADDING DIFFERENT TYPES OF PROBIOTICS IN FISH FEED ON THE GROWTH AND SURVIVAL RATE OF CARP (Cyprinus carpio) - Djulia, Sirda; Juliana, Juliana; Sutianto, Sutianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This study aimed to determine the effect of giving different types of probiotics in fish feed on carp's growth and survival rate (Cyprinus carpio). It was an experimental study with a completely randomized design that included four treatments and three replications. The treatment was divided into (A) 0 mL/kg addition of probiotics, (B) 10 mL/kg addition of probiotics, (C) 15 mL/kg addition of probiotics, and (D) 3 mL/kg addition of probiotics. The stocking density was 20 fish/aquarium, and the feeding frequency was three times per day. This study showed that adding different types of probiotics had a significant effect (p<0.05) on length growth, weight growth, and survival rate of carp. The best results for getting the highest length growth were obtained in treatment B with a value of 1,96 cm, and the highest increase in weight growth was also obtained in treatment B with a value of 1,49 g. Moreover, the highest survival rate observed was also obtained in treatment B, with a percentage of 85%.